Investigation of the Opinions of a Waldorf Kindergarden on the Different Aspects of Mission, Vision and Differentiations in Turkey - Fatma Ünal; Ceren Koca (Anı Publishing, 2018)
The aim of this research which subjects the Waldorf approach is to examine why parents are choosing the Waldorf Preschool and principle, teachers and parents perspectives of mission and vision of preschool and parents perspectives of differences between Waldorf Preschool and other type of preschools. Thus this research is a qualitative study in the design of a holistic single-case. The population of the study consisted of parents and administrators and teachers in a kindergarten in Istanbul and accredited under the IASWECE. The data were encoded in the analysis and the relationships between these codes were identified. According to the findings about the why parents are choosing the Waldorf Preschool are paralleling with the findings about principle, teachers and parents perspectives of mission and vision of preschool and parents perspectives of differences between Waldorf Preschool and other type of preschools. As well as parallel findings, effect of Waldorf approach come into prominence.